Percent Body Fat Cut-Off Points for Diagnosing Metabolic Syndrome in Korean Adolescents - Saejong PARK; Dong-Sik CHUNG; Byoung-Goo KO; Hong-Sun SONG; Kwang Jun KIM; Jin-Wook CHUNG; Seunghee LEE; Chul-Hyun KIM; Younshin NAM; Seungyun SHIN; Hyo LEE; Sochung CHUNG; et al. (Tehran University of Medical Sciences, 2019)
Background: This study aimed to identify percent body fat cut-off points related to metabolic syndrome in a large sample of Korean adolescents. Methods: The subjects (n=2120; boys=1107, girls=1013) were middle and high school students aged 12-17 yr who participated in the Korean National Fitness Award Project in 2013. Percent body fat was estimated via eight-polar bioelectrical impedance analysis. Metabolic syndrome was classified using established standards based on the National Cholesterol Education Program with the definition modified for age. Age- and sex-specific percent body fat z-scores were calculated for every adolescent using skewness, median, and coefficient of variation curves to account for growth and development. Receiver operating characteristic curve analysis was used to identify the percent body fat cut-off points using percent body fat z-scores from skewness, median, and coefficient of variation curves as the test and metabolic syndrome as the criterion. Results: Based on the modified National Cholesterol Education Program criteria for metabolic syndrome, the areas under the receiver operating characteristic curve for percent body fat were 0.882 and 0.893 for boys and girls, respectively. The percent body fat percentiles were 82.2 and 87.3 for boys and girls, respectively. According to the skewness, median, and coefficient of variation curves, the percent body fat cut-off points based on the modified National Cholesterol Education Program criteria were 23.6%-25.7% for boys and 32.8%-37.3% for girls, both aged 12-17 yr. Age- and sex-specific percent body fat cut-off points were identified in relation to the metabolic syndrome status of Korean adolescents. Conclusion: These percent body fat cut-offs might be useful for identifying metabolic abnormality due to obesity in Korean adolescents.